1994
DOI: 10.1093/jn/124.12.2477
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Intake and Status Influence Retinol Balance, Utilization and Dynamics in Rats ,

Abstract: To study effects of vitamin A status on retinol dynamics, male rats were fed purified diets varying in vitamin A concentration. Group 1 rats had marginal liver vitamin A levels (approximately 500 nmol) and were in a slight positive vitamin A balance; Group 2 had similar liver levels but were in a slight negative balance; Group 3 had lower liver levels (approximately 370 nmol) and were in a slight negative balance; Group 4 had depleted liver reserves (<10 nmol) and were in vitamin A balance. [3H]Retinol-labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 13 publications
2
40
1
Order By: Relevance
“…This important observation deserves emphasis: it makes sense that using population means for factors F and S might give a good estimate of stores in a given population, but there is no reason to expect good prediction of a specifi c individual's TBS since F and S vary among individuals. Large inter-individual variation has also been found in kinetic parameters when vitamin A kinetic data from studies in both rats [8] and humans [13] were analyzed by model-based compartmental analysis. The issue of defi ning TBS for individuals will require further refi nement of the technique if this is deemed a needed measurement.…”
Section: "Olson Equation" and Underlying Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This important observation deserves emphasis: it makes sense that using population means for factors F and S might give a good estimate of stores in a given population, but there is no reason to expect good prediction of a specifi c individual's TBS since F and S vary among individuals. Large inter-individual variation has also been found in kinetic parameters when vitamin A kinetic data from studies in both rats [8] and humans [13] were analyzed by model-based compartmental analysis. The issue of defi ning TBS for individuals will require further refi nement of the technique if this is deemed a needed measurement.…”
Section: "Olson Equation" and Underlying Assumptionsmentioning
confidence: 99%
“…Indeed, when stores are high, the liver is undoubtedly the major (albeit not the only) site of vitamin A storage. In contrast, in rats with low liver vitamin A stores, more than 90 % of total body vitamin A is actually present in extrahepatic tissues [8]. This distinction is important because many of the human populations of interest in fi eld studies have low liver vitamin A stores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be investigated if the equilibration time and the fractional catabolic rate are infl uenced by vitamin A status in the higher range of liver reserves in these populations. Studies in rats demonstrated a higher catabolic rate with higher vitamin A intake, reserves, and serum concentrations [28]. Kinetic experiments are needed in various populations like schoolchildren and pregnant women to defi ne life-stage infl uences on equilibration time and fractional catabolic rate.…”
Section: Further Establish Guidelines For Interpreting Valid Techniquesmentioning
confidence: 99%
“…Breast milk is the only source of vitamin A (retinol) during the neonatal period for exclusively breast-fed infants. On the other hand, there are two determining factors for the neonates to achieve their vitamin A requirements: the concentration of this vitamin in the milk and the milk volume consumed, both influenced by maternal vitamin A status and dietary intake (1,2).…”
mentioning
confidence: 99%